Water level, pressure, temperature and conductivity (2023-2024) from Portillo stream at 3800 m asl. Hourly data. (Tunuyán, Mendoza, Argentina) - Tapia Baldis, Carla Cintia (2024)
Water level, pressure, temperature, and conductivity have been continuously measured in the Portillo stream from 2023 to 2024 (ongoing). The stream is located in the upper part of the homonymous valley in Tunuyán, Mendoza, Argentina. The Portillo valley features a mountain glacial/periglacial environment, characterized by a diversity and richness of ice bodies, including various types of glaciers. In many instances, particularly in the larger glaciers, complex landforms can be observed. These landforms often begin as exposed glaciers in their upper sections and become covered by debris towards their terminal ends, sometimes transforming into rock glaciers (i.e., ice-debris complexes).